Conceptualization and measurement of virtuous leadership: doing well by doing good - Wang, Gordon; Hackett, Rick D.; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2015)
Despite a long history in eastern and western culture of defining leadership in terms of virtues and character, their significance for guiding leader behavior has largely been confined to the ethics literature. As such, agreement concerning the defining elements of virtuous leadership and their measurement is lacking. Drawing on both Confucian and Aristotelian concepts, we define virtuous leadership and distinguish it conceptually from several related perspectives, including virtues-based leadership in the Positive Organizational Behavior (POB) literature, and from ethical and value-laden (spiritual, servant, charismatic, transformational, and authentic) leadership. Then, two empirical studies are presented that develop and validate the Virtuous Leadership Questionnaire (VLQ), an 18-item behaviorally-based assessment of the construct. Among other findings, we show that the VLQ accounts for variance in several outcome variables, even after self-assessed leader virtue and subordinate-rated social and personalized leader charisma are controlled. Valuation Insight: Wang and Hackett discuss the ingredients of virtuous leadership and argue that such leadership should positively affect firm value. Virtuous leadership is not at odds with leader effectiveness and will facilitate the economic livelihood and longer term sustainability of an organization.
65 p. ; Includes bibliographical references (pp. 42-56). ; "January 2015."
Keywords: Virtuous leadership; Positive organizational behavior; Scale development; Virtues